Relación entre la densidad de la masa y la producción de corcho en montes alcornocales del sur de españa - Álvarez, E Torres; González, G Montero; Suárez, M A; Cámara, D E L A; Torres Álvarez, E; Montero González, G; Suárez de la Cámara, M A (II Congreso Forestal Español, 1997)
In this paper the influence of cork-oak stand density on quantity and quality cork production is studied. Seventy five experimental plots were installed at Cortes de la Frontera (Málaga, Spain) cork-oak forests. Sorne stand and productive variables for different basal area were studied. The statistical analysis of the data permit to propose 20-25 m2!ha basal area as the optimum stand density
Keywords: cork-oak; Quercus suber; silviculture; stand density